FORMULASI LULUR KRIM YANG MENGANDUNG KOMBINASI YOGHURT DAN PATI BERAS HITAM (Oryza sativa L.) - Vina Purnamasari M; Ermina Pakki; Mirawati Mirawati (Fakultas Farmasi UMI, 2016)
Herbal cream formulation that contain yoghurt and black rice (Oryza sativa L.) combination investigation has been done, used anionik amin soap (stearic acid and triethanolamin), nonionik (tween 80), anionik detergent (Sodium lauryl sulfate) as the emulgator. An investigation purpose was to have a herbal cream formulation most optimum in stability. Stability evaluation performed before and after accelerated condition in 5oC and 35oC for 10 cycles. Organoleptis, creaming volume, viskositas, emulsion type, homogenitas and dispersed globul then observed. The results showed parameters of organoleptic testing, kriming volume, homogeneity, and the type of emulsion drops dispersed in the ninth formula obtained no change before and after strees conditions . But the viscosity measurements showed formulas that use anionic emulgator such us amin soap (formula I - III) or detergents (Formula VII - IX) results do not change viscosity (α = 5%) after being kept in conditions that are imposed. So it can be concluded the formula I - III and VII - IX produces a more stable Herbal cream physically.